Pengaruh Kualitas Pelayanan Dan Waktu Tunggu Terhadap Kepuasan Pasien Di Poliklinik Thalasemia Rumah Sakit Umum Daerah Kabupaten Karawang - Dhiantoro, Guntur Rhama; Megawati, Liya (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
Patient satisfaction is a valid reaction after receiving services. This affects the decision to reuse which is continuous to purchase the same service and will affect the delivery of messages or impressions to others about the services provided. This study aims to determine, analyze, and explain the effect of service quality and waiting time on patient satisfaction at the Thalassemia Polyclinic of the Karawang Regency Regional General Hospital. The research method used is quantitative method with descriptive and verification approaches. The sampling technique used in the study was accidental sampling. The sample used was 398 data. The data analysis used in this study is the Classical Assumption Test, Descriptive Analysis, Verification Analysis using Multiple Linear Regression and Hypothesis Testing. The results showed that service quality had a positive and significant effect on patient satisfaction with a percentage of 18.3%, waiting time had a positive and significant effect on patient satisfaction with a percentage of 40.5%. There is an effect of service quality and waiting time simultaneously on patient satisfaction of 58.8% and the remaining 41.2% is influenced by other variables not examined in this study.